Lithuanian I-S-T version: Reliability and validity - Dragūnevičius, Kęstutis; Gintilienė, Gražina (Psichologija, 1998)
This paper refers to the psychometric properties of IST-70 Intelligence Structure Test). The aim of investigation was to evaluate the reliability and validity of A and B forms of IST-70 for the Lithuanian population of 12th grade children (sample of 295 schoolchildren). The obtained data show that there are significant differences between the results of Lithuanian 12th grade schoolchildren and German standardisation sample of the same age. Analysis of results show that some psychometric properties of IST-70 cannot meet strict psychometric criteria for tests. Item analysis show there are many of subtests which have non-discriminating items. Also there was found very little subtests of IST-70 met the criteria of reliability. Many correlational links were established between the results of subtests also. The factor analysis of results showed the A form of IST-70 has no theoretically clear factorial structure while the B form has two hypothetical factors: verbal material and nonverbal material. The origin of this factors still remains unexplained.